Osteophyte Development During Osteoarthritis (OA) – Consideration of Angiogenesis, Mechanical Loading and Tissue Microstructure - BEDNARCZYK, Ewa; LEKSZYCKI, Tomasz (Engineering Transactions, 2016)
This paper is devoted to modelling and investigation of the effects of mechanical loading, blood vessels development and tissue microstructure in osteoarthritis (OA) – a degenerative joint disease . OA is one of the most common diseases affecting the population, and therefore it is a social and medical problem of utmost importance. It predominantly affects the elderly but also sportsmen, obese people and those with curvature of the spine. Although the phenomenon of OA is not yet fully understood, it is commonly accepted that mechanical aspects are crucial in its evolution [1, 2]. Mechanical overloading leads to apoptosis of chondrocytes, which increases the generation of vascular endothelial growth factors [3]. A properly formulated mathematical model of cartilage degeneration and osteophytes development can significantly help in understanding the complexity of this process. The presented model reflects the most important aspects of the interactions between mechanical and biological factors, crucial for the phenomenon of OA. and osteophytes development can significantly help to comprehend complexity of this process. Presented model reflects the most important aspects of the interaction between mechanical and biological factors crucial for osteoarthritis phenomenon.